Multi‐epoch time‐resolved photometry of the eclipsing polar CSS081231:071126+440405. Issue 2 (March 2015) - Schwope, A. D.; Mackebrandt, F.; Thinius, B. D.; Littlefield, C.; Garnavich, P.; Oksanen, A.; Granzer, T.
Abstract The eclipsing polar CSS081231:071126+440405 turned bright (Vmax ∼ 14.5) in late 2008 and was subsequently observed intensively with small and medium‐sized telescopes. A homogeneous analysis of this comprehensive dataset comprising 109 eclipse epochs is presented and a linear ephemeris covering the five years of observations, about 24000 orbital cycles, is derived. Formally this sets rather tight constraints on the mass of a hypothetical circumbinary planet, Mpl ≤ 2 MJup. This preliminary result needs consolidation by long‐term monitoring of the source. The eclipse lasts 433.08 ± 0.65 s, and the orbital inclination is found to be i = 79.3°–83.7°. The centre of the bright phase displays accretion‐rate dependent azimuthal shifts. No accretion geometry is found that explains all observational constraints, suggesting a complex accretion geometry with possible pole switches and a likely non‐dipolar field geometry. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)